Chitosan coated magnetic nanoparticles as carriers of anticancer drug Telmisartan: pH-responsive controlled drug release and cytotoxicity studies. (January 2021) - Dhavale, Rushikesh P.; Dhavale, R.P.; Sahoo, S.C.; Kollu, P.; Jadhav, S.U.; Patil, P.S.; Dongale, T.D.; Chougale, A.D.; Patil, P.B.
Abstract: Chitosan, a natural, hydrophilic and biodegradable polymer was grafted on Fe3 O4 magnetic nanoparticles (MNPs) and used as a carrier of poorly water-soluble anticancer drug Telmisartan (TEL). The characteristics of MNPs and chitosan coated MNPs (MNP-CS) were determined by using X-ray diffraction, field emission scanning electron microscope, transmission electron microscope, vibrating sample magnetometer, and BET surface area analyzer. The chitosan coating of MNPs was validated by Fourier transform infrared spectroscopy (FTIR) and thermal gravimetric analysis. The drug was loaded on MNP-CS through an amide bond between amino groups of chitosan and carboxylic groups of TEL. The drug loading capacity of ~50% was obtained due to the large BET surface area (134 m 2 /g) of mesoporous MNP-CS. Drug loaded MNP-CS (MNP–CS–TEL) showed pH-responsive controlled release characteristics. The MNP–CS–TEL showed dose dependent cytotoxicity towards PC-3 human prostate cancer cells. The results demonstrated the significant antitumor activity of designed nanoformulation. Graphical abstract: Image 1 Highlights: Nanoformulation reported improves the therapeutic efficacy of poorly bioavailable anticancer drug Telmisartan. Chitosan, a natural and biocompatible polymer, is grafted on MNPs to use as carriers of Telmisartan. Higher drug loading was obtained due to the higher surface area and mesoporous nature of chitosan coated MNPs. Drug release was higher in the cancerous environment, whereas the nanoformulation was stable at physiological conditions. The cytotoxicity studies on PC-3 human prostate cancer cells demonstrated a dose-dependent reduction in cell viability.